OPPORTUNITIES FOR PSYCHOLOGICAL READINESS DEVELOPMENT OF PRESCHOOL CHILDREN FOR FORMAL SCHOOL EDUCATION - Guzal Qurbonova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Psychological readiness for school is one of the key determinants of successful adaptation to formal education and subsequent academic achievement. Contemporary educational systems increasingly recognize that school readiness extends beyond academic preparation and includes cognitive, emotional, social, motivational, and behavioral competencies. This article examines the opportunities for developing psychological readiness among preschool children for formal school education. The study analyzes theoretical foundations of school readiness, developmental characteristics of preschool children, and pedagogical approaches that facilitate psychological preparation for schooling. Particular attention is devoted to play-based learning, social-emotional development, family involvement, communication skills, and innovative educational technologies. The findings suggest that systematic psychological preparation enhances children’s self-regulation, learning motivation, social competence, emotional stability, and adaptability to school environments. Practical recommendations are proposed for educators and parents to support the comprehensive development of school readiness.